2017
DOI: 10.3906/sag-1507-180
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characteristics and antibiotic resistance of Acinetobacter baumanniibeta-lactamase-producing isolates, a predominance of intrinsic blaOXA-51, and detection of TEM and CTX-M genes

Abstract: The aim of this study was to determine the molecular characteristics and antibiotic resistance of 13 (10 inpatient and three outpatient) Acinetobacter baumannii beta-lactamase-producing isolates collected in Bosnia and Herzegovina between December 2009 and May 2010.Materials and methods: Susceptibility testing was performed by disk diffusion and broth microdilution methods. The modified Hodge and combined disk test with EDTA/phenylboronic acid was used to screen for carbapenemase production. Production of exte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 19 publications
(32 reference statements)
0
7
0
Order By: Relevance
“…ISAba1 (Ibrahimagić et al, 2017). In this study a shift to CHDL was observed Sequencing of blaOXA-40 gene revealed the OXA-72 allelic variant associated with high level of resistance to carbapenems.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…ISAba1 (Ibrahimagić et al, 2017). In this study a shift to CHDL was observed Sequencing of blaOXA-40 gene revealed the OXA-72 allelic variant associated with high level of resistance to carbapenems.…”
Section: Discussionmentioning
confidence: 50%
“…This prompted us to analyze these isolates with regards to genetic diversity, antibiotic susceptibility and occurrence of acquired carbapenem resistance genes. The previous studies from 2009 found that reduced susceptibility in A. baumannii from Bosnia was solely atributed to overexpression of intrinsic OXA-51 β-lactamase with ISAba1 upstream of the gene (Ibrahimagić et al, 2017). The new isolates were collected during two periods: in 2011 and 2015 and compared to determine the dynamic changes in carbapenemase resistance mechanisms and the population structure.…”
Section: Introductionmentioning
confidence: 99%
“…The current study showed that A. baumannii resistance to Ampicillin, , Ceftazedime , Cifepim, Imipinem and this resistance was due to the possession of (β -lactam) and this bacteria production β-lactamase [16] . β-Lactam ring, which leads to inactivation of the antibiotic.…”
Section: Resultsmentioning
confidence: 60%
“…The bla OXA-51 is generally found in all A. baumannii isolates, being either carbapenemresistant or carbapenem-sensitive isolates [19][20][21]. This gene is not associated with resistance unless insertion sequences (ISAbaI) upstream of bla OXA-51 are involved, causing over-expression leading to carbapenem resistance, especially to imipenem [21,22]. Therefore, it is recommended as an excellent marker for species identification but not as a resistance marker [22][23][24][25].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, bla OXA-23 is a significant cause of carbapenem resistance in A. baumannii [19,21,22]. It has been reported as a prevalent gene in various studies published in several countries, including Saudi Arabia and Iran [19,21].…”
Section: Discussionmentioning
confidence: 99%